KEBIJAKAN DIVIDEN DAN FAKTOR â FAKTOR YANG MEMPENGARUHINYA - Samrotun, Yuli Chomsatu Samrotun (Paradigma, 2015)
This study aims to determine whether there is a partial effect and simultaneous profitability (return on asset), likuidity (cash ratio and current ratio), leverage (debt to equity ratio), growth and firm size on dividend policy. Hypothesis in the formed are : 1) There are significant return on assets on dividend policy, 2) There are significant cash ratio on dividend policy, 3) There are significant current ratio on dividend policy. 4) There are significant debt to equity ratio on dividend policy. 5) There are significant growth on dividend policy. 6) There are significant firm size on dividend policy. 7) There are significant return on assets, cash ratio, current ratio, debt to equity ratio, growth, firm size on dividend policy . Based on the results of the research indicate that the variable return on assets, cash ratio, current ratio, debt to equity ratio, growth, and firm size normally distributed data, there is no multicollinearity, autocorrelation, heteroscedasticity. t test results showed variable return on assets, current ratio, and debt to equity ratioeffect on dividend policy, while the variable cash ratio, growth, and firm size does not affect the dividend policy, whereas the results F test showed that the independent variables use in this study simultaneously or jointly affect the dividend policy.